Quantifying the burden of injuries in temporary labour migrants: an analysis from the United Arab Emirates - K A Allen, PhD; A Hyder, PhD; W Robinson, PhD (Elsevier, 2015)
Background: Temporary labour migration is a global trend whereby individuals from one country move temporarily to another for employment. These populations are sometimes vulnerable groups with limited rights and resources during their migration experience. In the United Arab Emirates (UAE) more than 80% of the population are non-citizen temporary workers, mostly from low-income and middle-income south Asian and southeast Asian countries. With extremely restricted rights, they are mostly young men, who work predominately as unskilled or semi-skilled labourers in the construction, manufacturing, and oil sectors. Injuries incurred in the course of work are of concern in this population. To better understand the health and occupational risks facing these migrant workers, we aimed to systematically quantify the burden of injuries among temporary migrants in the UAE and compare it with the estimated injury burden for UAE citizens. Methods: We followed WHO and Global Burden of Disease Study protocols, to conduct a national burden of disease analysis for the UAE with a focus on quantifying the injury burden. We used local mortality and morbidity data sources from the Ministry of Health, Health Authority-Abu Dhabi, and Dubai Health Authority. Years of life lost (YLLs) and disability-adjusted life years (DALYs) were calculated by age, sex, and nationality. Findings: We estimate that, in 2010, migrants lost 448 584 DALYs to disease and injuries. For migrants, injuries were the leading cause of lost DALYs, irrespective of sex, and accounted for 27% (121 915 DALYs) of the total. Among UAE citizens, injuries were also the leading cause of DALYs lost, representing 22% of the national-specific total (216 301 DALYs). Cause-specific analysis of YLLs shows that road traffic injuries are the main cause of premature death for both migrants and nationals. Suicides (10 392 YLLs; 4·9%), other adverse events (6824 YLLs; 3·5%) and falls (5554 YLLs; 2·6%) are also important causes of total YLLs for all migrants, but in migrant men account for 5·2% and 3·4%, respectively, of the total YLL burden. Interpretation: This study highlights the high burden of road traffic injuries in the UAE and the need for national efforts to reduce deaths from this cause. Furthermore, it shows that the injury burden is higher for migrants. It highlights the need for an increased focus on injury prevention for migrants-especially suicide prevention-and efforts to reduce occupational falls. Despite the limitations associated with using secondary data, we provide a systematic assessment of the burden of injuries in temporary migrants working in the UAE. Funding: From the Baker, Taylor, Reinke Scholarship.